“Agua de poesía del primer poeta de Francia”: Venturini Villon’s Reader - Salerno, Maria Paula (Thélème. Revista Complutense de Estudios Franceses, 2017)
This article examines the significance of the literary dialogue the Argentinian writer Aurora Venturini (1921-2015) establishes with the medieval French poet François Villon, with his work and his legend. In particular, we analyze how this dialogue is configured in two of her literary works: the poem “Pasaje con Villon”, included in her last book of poetry, La trova from 1962, and the essay François Villon, raíz de iracundia. Vida y pasión del juglar de Francia, published in 1963.
Keywords: Aurora Venturini; François Villon; literary dialogue; poètes maudits